Factors affected to satisfaction of personnels toward operation at Department of Operative Dentistry and Endodontics, Faculty of Dentistry, Mahidol University. - Sirilug Chanapanchai (2016)
Objective: To study and compare the factors contributing to job satisfaction of personnel in the Department of Operative Dentistry and Endodontics who vary in gender, age, educational background, salary, and working experience. Materials and methods: Subjects of the current investigation were staffs at Department of Operative Dentistry and Endodontics. Data acquisitions were collected from 30 subjects using questionnaires containing 3 parts. Part 1: General information. Part 2: Aspects contributing to job satisfaction of personnel in 5 viewpoints, i.e., 1) job details; 2) job security; 3) career development; 4) income/welfare; and 5) social relationship within the bureau. Part 3: Suggestions. Literature review was also done through publications. The collected data were analyzed by frequency, percentage, mean, standard deviation using t-test and One-way Analysis of Variance (ANOVA) with SPSS statistical software program.Results: Job satisfaction of personnel in the Department of Operative Dentistry and Endodontics, Faculty of Dentistry, Mahidol University was noted at high-level with x = 4.01. In detail, high satisfaction was shown for aspects of job security (x = 4.67); social relationship within the bureau (x = 4.47); job details (x = 3.98); and career development (x = 3.68). The least satisfaction was derived from aspect of income/welfare, which presented moderate level with x = 3.20 Job satisfaction was affected by job security but not by income/welfare. Conclusion: Factors that influence the job satisfaction of personnel are derived from different personal basic information. However, differences of personal basic information, i.e., gender, age, educational background, salary, and working experience, were not depend on job satisfaction, which was not conform to the set hypothesis.